Transformation of Beliefs: an Evaluation of Economic Risk under Uncertainty - Śliwiński, Adam; Klapkiv, Liubov (Olsztyn Economic Journal, 2017)
This paper presents the results of a study of the risk-taking behavior of investors in some Eastern European countries in the post-soviet period. A unique transformation processes in society at the transition from the 20th to the 21st century caused the value of this point of view. Individual risk philosophy was on the way to being built under the factors of a changing society from command (full regulation of the environment) to a free market relationship. We investigate the influence of heuristics on the awareness of subjective risk evaluation in the case of a “sollective” investment activity in a trust company,MMM in 1994. The study confirms the bias in human behavior in the case of a high–risk situation. Some results, such as the influence of educational level on risk and reduced income values in terms of absolute growth, contradict the previous findings.